Emotional Intelligence and Managerial Performance in Healthcare Organizations in Indonesia - Puspita, Lina (International Journal of Leadership and Governance, 2024)
Purpose: The aim of the study was to analyze the emotional intelligence and managerial performance in healthcare organizations in Indonesia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Emotional Intelligence (EI) positively impacts managerial performance in Indonesian healthcare organizations. Managers with higher EI levels exhibit enhanced interpersonal skills, decision-making abilities, and conflict resolution strategies. This competency enables better understanding and management of both personal and team emotions, fostering improved employee satisfaction and organizational climate. Unique Contribution to Theory, Practice and Policy: Emotional intelligence theory, transformational leadership theory & job demands-resources (JD-R) theory may be used to anchor future studies on emotional intelligence and managerial performance in healthcare organizations in Indonesia. Healthcare organizations should incorporate comprehensive EI training into their leadership development initiatives. Policymakers should include EI competencies as part of the standards and accreditation criteria for healthcare management positions.